ANALISIS KONFLIK PENGELOLAAN PERIKANAN TANGKAP DALAM PERSEPEKTIF INTERAKSI STAKEHOLDERS DI TELUK LAMPUNG - Hendriwan Hendriwan; M. Fedi A. Sondita; John Haluan; Budy Wiryawan (Buletin PSP, 2007)
Activities of catch fishery in Lampung Bay have created a number of conflicts among stakeholders. The objectives of this research were to identify types of conflict, efforts of conflict resolution, potency of conflict from stakeholders interaction, and identification od strategies to eliminate the conflicts. This research applied PISCES approach, PRA and SWOT analysis. Types of conflict in capture fishery in Lampung bay were related with relocation of a fish landing port (PPI), relocation of fishermen housing, mooring place and fish selling price, use of fish bombs, illegal fees, competition on control of fishing ground, and competition on control of the fish landing port/fish auction site (PPI/TPI). Interaction among big fishermen and newly settled fishermen was the most potential conflict (15.38 %), whereas competition between the two village cooperatives (KUD Mina Jaya and KUD Lestari) was the least potential conflict (3.85 %). Availability and quality of human resources was the main strength of the capture fishery management in Lampung Bay (positive effect score / spp S = 0.51) while the internal conflict among local stakeholders was the main weakness of the management (spp W = 0.11), and access to the most prospective market(Jakarta) and conducive sociopolitical condition were the main opportunities for development of the capture fishery in the future (spp 0 each = 0.36), however, the use of destructive technology was the main threatto the sustainability of the fishery (spp T = 0.17). At present, management of the capture fishery in Lampung Bay was at growth stage with focusing stability or horizontal integration (quadrant 5 of Internal and External E matrix). In order that development leads to quadrant I (conflict is eliminated), then the interaction of internal factor and interaction of external factor need to be improved so that FI score increases by 1.67 and FE score increases by 1.74.